QASHQADARYO VILOYATI KOKSINELLIDLARINING SISTEMATIK TAHLILI - Arabova N.Z, Arabova N.Z; Buriyeva X.P., Buriyeva X.P.; Sattorova M.A., Sattorova M.A.; Komilova D, Komilova D (Actual problems and prospects of the study of the fauna, 2024)
The article describes the taxonomy and species composition of the Coccinellidae family representatives found in the Kashkadarya region. Scientific research in this area has identified five subfamilies within the Coccinellidae family, comprising 38 species across 19 genera. Additionally, information on the distribution of species and subspecies in the region is provided